2006
DOI: 10.1039/b515269k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of transition metal-catalyzed hydrogen transfer reactions

Abstract: In this tutorial review recent mechanistic studies on transition metal-catalyzed hydrogen transfer reactions are discussed. A common feature of these reactions is that they involve metal hydrides, which may be monohydrides or dihydrides. An important question is whether the substrate coordinates to the metal (inner-sphere hydrogen transfer) or if there is a direct concerted transfer of hydrogen from the metal to substrate (outer-sphere hydrogen transfer). Both experimental and theoretical studies are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
455
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,028 publications
(477 citation statements)
references
References 78 publications
11
455
1
4
Order By: Relevance
“…6,6'-Dihydroxy-2,2'-bipyridine normally exists as its tautomer, 2,2'-bipyridone (see Figure 1), which in this form is not 30 able to coordinate to a metal centre in a bidentate fashion. The 2,2'-bipyridone tautomer was therefore converted to 6,6'-bis(tertbutyl-dimethylsiloxy)-2,2'-bipyridine, which is subsequently hydrolysed after coordination to the metal centre.…”
mentioning
confidence: 99%
“…6,6'-Dihydroxy-2,2'-bipyridine normally exists as its tautomer, 2,2'-bipyridone (see Figure 1), which in this form is not 30 able to coordinate to a metal centre in a bidentate fashion. The 2,2'-bipyridone tautomer was therefore converted to 6,6'-bis(tertbutyl-dimethylsiloxy)-2,2'-bipyridine, which is subsequently hydrolysed after coordination to the metal centre.…”
mentioning
confidence: 99%
“…It is hydride 4 which then performs the reduction of ketones, through the well-established outer-sphere six-centred transition state mechanism already established in the closely related transfer hydrogenation process. [7] 1 X=OTf The mechanism of hydrogen activation by 1 has now been extended, [6b,c] and related Ru(II) complexes containing TsDPEN ligands have been reported, including examples in which additional functionalities assist the hydrogen dissociation step. [6e,f] Following the initial disclosure by Noyori et al,[6a] it was found that the closely related Ir complex 5 was also active in the asymmetric reduction of -hydroxy acetophenone derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Catalysts of this type [3] can be prepared in situ by combining Ru(II), Rh(III) and Ir(III) complexes with chiral diamine ligands, [4] however a number of very efficient, well-defined complexes derived from chiral amines have recently been reported. [5,6] An important breakthrough in this area was provided by complex 1, [6] the OTf derivative of the well-established asymmetric transfer hydrogenation catalyst 2, [7] itself an organometallic complex of the ligand N-tosyl-1,2-diphenyl-ethane-1,2-diamine (TsDPEN). Although complex 2 is reported to be a poor catalyst for ketone hydrogenation, replacement of its chloride with triflate, and conducting the hydrogenation in methanol rather than isopropanol, results in the formation of a much more active hydrogenation system (Scheme 1) which was first tested on a series of chromanone substrates.…”
Section: Introductionmentioning
confidence: 99%
“…very often applying Ru(II)-based homogeneous catalysts. Excellent rates and selectivities were achieved by Noyori [37], Bäckvall [8], Xiao [38] and others in synthesis of secondary alcohols. In general, water is not well tolerated in such processes [38], and several studies showed that both the rates and selectivities decrease substantially with increasing water content of the 2-propanol-water mixtures even in those cases when watersoluble catalysts were applied.…”
Section: Introductionmentioning
confidence: 97%